2014
DOI: 10.2399/tahd.14.00070
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de birinci basamağın gücü

Abstract: Güçlü bir birinci basamak (BB) sağlık hizmet sunumuna sahip ülkelerde toplumun sağlık ihtiyaçlarına daha iyi yanıt verilebileceği, sağlıkta daha eşitlikçi bir hizmet sunumu sağlanacağı ve sağlık harcamalarının daha maliyet etkin olacağı ön görülmektedir. Türkiye’de son 10 yılda sağlık alanında önemli değişikliklere yol açan ve Sağlıkta Dönüşüm Programı (SDP) olarak adlandırılan bir sağlık reform programı kademeli olarak uygulanmıştır. Bu programın önemli bileşenlerinden birisi aile hekimliği uygulamasıdır. Bu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…However, GP services for Turkey are far from their counterpart services in other European countries. The main problem is an inadequate work force, high numbers of patients per GP and the lack of multidisciplinary implementation (27,28). In contrast to GP services, specialist care and inpatient care are subject to payment.…”
Section: Discussionmentioning
confidence: 99%
“…However, GP services for Turkey are far from their counterpart services in other European countries. The main problem is an inadequate work force, high numbers of patients per GP and the lack of multidisciplinary implementation (27,28). In contrast to GP services, specialist care and inpatient care are subject to payment.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, 9% of patient family physicians who were outside of the Bursa province may have contributed to this increase. In one study, it was reported that family physicians were not eager to deal with guest patients (Akman, 2014). If so, it would not be surprising that the patients referred themselves to hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, following pilot schemes, family medicine has begun to be applied throughout the country since 2010 (Akman, 2014). The determinants of medical service quality in Turkey have been affected positively with the family practice system (Hone et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Aynı zamanda KH hizmetlerinin yeterli olmadığı ve SDP öncesine göre pek ilerleme kaydedilmediği bildirilmiştir. 20…”
Section: Karşilanmayan İhti̇yaçlarunclassified